Study of Encapsulation of Alkylamines Inside Single-Walled Carbon Nanotubes - Ganji, M.D.; Rezvani, M. (Asian Journal of Chemistry, 2010)
The density functional theory has been used to investigate the interaction between the tertiary butylamine molecule and single-walled carbon nanotubes. It has been found that tertiary butylamine molecules prefer to be adsorbed on the top of C atom of the tube side-wall. Compared to the case for carbon nanotubes with large diameters, the adsorption energy is found to be reduced in the low-curvature case. The encapsulation of the tertiary butylamine molecule inside the carbon nanotubes has also been investigated and the results show that tertiary butylamine molecules were incorporated inside the nanotubes can form more stable complex in comparison to the adsorbed molecule on the outer surface of the nanotubes. The present study provides an improved understanding in alkylamines interactions with inner/outer surface of carbon nanotubes of varying diameters.